Reliability of 2D motion analysis software for evaluation of dynamic smile asymmetry using smartphone technology - Dhelal Al-Rudainy; Hadeel Adel Al-Lami; Talib Al-Ameri; Liu Yang (Clinical and Investigative Orthodontics)
Aim To evaluate the reliability of a free motion analysis method in the evaluation of the 2D dynamic asymmetry of smiles using smartphone technology.Materials and methods Twenty-six healthy adult females were included in this study. Four facial bilateral landmarks were marked on participants’ mouths and noses. A smartphone camera was used to record a video of the maximum smile of each participant. Each video was imported into a free motion analysis software program separately, that was used to track the landmarks’ speeds and distances during smiling. The asymmetry scores of the landmark motions were calculated by measuring the absolute differences between the right and left sides, and in perfectly symmetrical smiles the asymmetry scores would be zero. After an interval of a month, the asymmetry scores were re-calculated. The means of the absolute differences in the repeated distances and speeds for all the landmarks were calculated.Results The total errors of the repeated distances and speeds were around 0.4 millimetres (mm), except for asymmetrical maximum smile speeds, the errors were around 0.7 mm/sec. Intra-class correlation test showed high correlations between repeated asymmetry scores after a one-month interval. The asymmetry scores of the distances of landmarks’ motions at mid-smile were less than at maximum smile, although the peak asymmetry of speed occurred at the mid-smile frames rather than the maximum smile frames.Conclusions Motion analysis method is a reliable technique for analysis of 2D dynamic asymmetry of facial smiles, with acceptable accuracy. Using smartphone technology is clinically convenient and affordable.